2010
DOI: 10.4103/0972-6748.90343
|View full text |Cite
|
Sign up to set email alerts
|

Does androgyny have psychoprotective attributes? A cross-sectional community-based study

Abstract: Background:In our society, adherence to feminine traits by the female gender had been culturally promoted and socially desired. A few studies, however, entertained the possibility that healthy men and women have some common attributes in their gender orientation. Androgyny and masculinity were found related to positive mental health.Materials and Methods:A cross-sectional study was conducted to assess the level of masculinity and femininity and its relationship with the perception of stress and various psychop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Among patients with HF, lack of men with type M was accompanied by overrepresentation of men with type U. This is alarming because the U type among healthy people is characterized by the highest level of stress (known as a risk factor for cardiovascular diseases) and by the highest risk of developing depression, which is a common comorbidity of HF (Drohomirecka, Jankowska, Banasiak, & Ponikowski, 2008; Jankowska et al, 2010; Lipińska-Grobelny, 2008; Patten et al, 2010; Prakash et al, 2010). In other words, type U can be interpreted as the least favorable type in the context of general health status and emotional comfort.…”
Section: Discussionmentioning
confidence: 99%
“…Among patients with HF, lack of men with type M was accompanied by overrepresentation of men with type U. This is alarming because the U type among healthy people is characterized by the highest level of stress (known as a risk factor for cardiovascular diseases) and by the highest risk of developing depression, which is a common comorbidity of HF (Drohomirecka, Jankowska, Banasiak, & Ponikowski, 2008; Jankowska et al, 2010; Lipińska-Grobelny, 2008; Patten et al, 2010; Prakash et al, 2010). In other words, type U can be interpreted as the least favorable type in the context of general health status and emotional comfort.…”
Section: Discussionmentioning
confidence: 99%
“…2017 ), higher creativity ( Norlander et al. 2000 ), and has been found to be psychoprotective ( Prakash et al. 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, some authors have shown that traditional masculinity is associated with drug abuse behavior in a study of students from the USA [6]- [9], several health behaviors in North American men [10], better mental health in Spanish men and women [11], less frequent use of mental health service when analyzing different studies in various nationalities [12], or greater self-esteem and lower levels of anxiety and depression in Hindu couples [13].…”
Section: Relationship Between Gender and Healthmentioning
confidence: 99%